L-carnitine-loaded nanoparticle ameliorates cypermethrin-induced reproductive toxicity in adult male rats - Noora Kadhim Hadi Alyasari; Wisam Hussein Selman (Wolters Kluwer Medknow Publications, 2023)
The objective of this investigation was to find out whether L-carnitine-loaded nanoparticle (LCn) could reduce the reproductive toxicity of cypermethrin (CYP), the widely used insecticide in veterinary medicine in male rats. Twenty male Wistar rats that weighed between 210 and 240 g were split into four groups and treated daily for 2 months. The control group was given 0.9% normal saline solution daily. The second group received CYP (3.83 mg/kg b. w. p. o.) daily. The third group was administered with LCn and CYP (50 mg/kg b. wt. p. o. and 3.83 mg/kg b. wt. p. o., respectively) daily, whereas the fourth group received LCn alone (50 mg/kg b. wt. p. o.) daily. On day 60, all rats were sacrificed and samples were collected. CYP-treated animals exhibited inhibition of testicular anti-oxidative stress mechanisms, testicular steroidogenesis enzyme activity (3β-hydroxysteroid dehydrogenase [3β-HSD] and 17β-HSD), and downregulation of steroidogenic acute regulatory (StAR) gene expression. In addition, it decreased testosterone, follicle-stimulating hormone, and LH levels and had detrimental consequences for sperm quality. LCn attenuated CYP-induced reproductive toxicity via the alleviation of testicular oxidative stress status, improvement of steroidogenic enzyme activity, and upregulation of StAR gene expression, which are probably responsible for the concomitant improvement in testicular hormonal levels and improvement in sperm properties. Intriguingly, LCn treatment alone could enhance the functions of the male reproductive system.